2019
DOI: 10.1016/j.susc.2019.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Real-time observation of self-interstitial reactions on an atomically smooth silicon surface

Abstract: Self-diffusion and impurity diffusion both play crucial roles in the fabrication of semiconductor nanostructures with high surface-to-volume ratios. However, experimental studies of bulk-surface reactions of point defects in semiconductors are strongly hampered by extremely low concentrations and difficulties in the visualization of single point defects in the crystal lattice.Herein we report the first real-time experimental observation of the self-interstitial reactions on a large atomically smooth silicon su… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 72 publications
(122 reference statements)
0
1
0
Order By: Relevance
“…Diffusion of the adsorbed interstitials and vacancies is described by corresponding subsurface diffusion coefficients which can differ from surface and bulk D i , v diffusion coefficients. Earlier it had been shown that an increase in the concentration of the self-interstitials in silicon during high-temperature submonolayer gold deposition results in the changing the kinetics of the atomic steps 22,23 . The later can be attributed to the change in the atomic step rate of advance as described by Eqs (3a) and (3b).…”
Section: Discussionmentioning
confidence: 99%
“…Diffusion of the adsorbed interstitials and vacancies is described by corresponding subsurface diffusion coefficients which can differ from surface and bulk D i , v diffusion coefficients. Earlier it had been shown that an increase in the concentration of the self-interstitials in silicon during high-temperature submonolayer gold deposition results in the changing the kinetics of the atomic steps 22,23 . The later can be attributed to the change in the atomic step rate of advance as described by Eqs (3a) and (3b).…”
Section: Discussionmentioning
confidence: 99%